2017
DOI: 10.18549/pharmpract.2017.03.1026
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmacist-led medication therapy management on medication adherence in patients with type 2 diabetes mellitus: a randomized controlled study

Abstract: Background:Poor adherence to antidiabetic medications leads to a higher rate of hospital admissions and adverse health outcomes in type 2 diabetes mellitus patients.Objective:This study aims to evaluate whether a pharmacist-led medication therapy management, compared to the usual care, could enhance medication adherence and reduce hospital admission in patients with type 2 diabetes mellitus.Methods:A prospective randomized controlled study was conducted in patients with type 2 diabetes mellitus from February 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 27 publications
5
53
0
1
Order By: Relevance
“…Non-adherence to medication by type 2 DPs of Pakistan is common [42]. But several studies proves that pharmacists' intervention can improve adherence to medication of type 2 DM [43,44]. But current study shows that about 59.5% drug sellers highlighted the effect of non-compliance to medication.…”
Section: Discussionmentioning
confidence: 81%
“…Non-adherence to medication by type 2 DPs of Pakistan is common [42]. But several studies proves that pharmacists' intervention can improve adherence to medication of type 2 DM [43,44]. But current study shows that about 59.5% drug sellers highlighted the effect of non-compliance to medication.…”
Section: Discussionmentioning
confidence: 81%
“…This includes pharmacists and others improving patients' knowledge about their disease, as well as ensuring they have a satisfactory experience when visiting ambulatory care clinics, to improve future medicine use. [50][51][52][53][54][55] Such activities though must take account of the fact that the patient population attending CHCs in South Africa (Table 1) typically have no formal education or only primary education, similar to other ambulatory care settings in South Africa and other African countries. [9,20,24,[56][57][58] Consequently, storytelling and other similar approaches may be appropriate, alongside initiatives such as diaries, pictograms and counselling involving pharmacists, to improve patient knowledge and subsequent medicine use.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to previous literature demonstrating the impacts of pharmacist led education program to improve medication adherence. 15,44,45 A meta-analysis of randomised control trials conducted by Cheema et al reported that 6 out of 7 studies had significantly increased in medication adherence from 56% to 68% in the intervention groups compare to control groups (Odds ratio 12.1, 95% CI 4.2-34.6; P<0.001). 18 Medication adherence could be improved by understanding to the nature of the disease and the rationale of the medication.…”
Section: Discussionmentioning
confidence: 99%